Spatial Values and Means of Their Expression in the Kalmyk Language (an Insight into Case Forms) - Liudmila L. Lidzhieva (Монголоведение, 2019)
Introduction. The study deals with spatial localization in the modem Kalmyk language. Being an important element of the world model, space finds its manifestation in certain language facts. In every language spatial semantics is expressed by certain lexical and grammatical units, and has somewhat pronounced specifics, particular semantic messages. Goals. The research seeks to describe types of localizations of spatial relations in the Kalmyk language expressed through case forms. M aterials. The work investigates selected literary, folklore and journalistic texts, as well as dictionaries extracted from the National Corpus of the Kalmyk Language and the Kalmyk National Corpus respectively. Results. In the Kalmyk language, a total of four grammatical cases may express spatial relations: the dative-locative, instrumental, ablative, and aditive ones serve to indicate location and motion in space, destination and starting points, and also movement of an object along or in/through space. The work reveals and describes localization types — in the Kalmyk language — with various values regarding a reference point. Among the general spatial values, the paper specificates location, approaching, departure and movement of an object ‘on, nearby, over’ with relation to a reference point. Private localizations (IN, APUD, AD, SUPER, ULTRA, SUPRA) expressed by case forms are used to indicate space inside, close, in the distance, on the surface, over a reference point, etc. The research attempts to reveal values of key localizations in the language examined.